Našemu Marku v spomin --- - Juhart, Miha (Pravnik, 2024)
The basis for this contribution is a speech delivered by the President of the Association of Law Societies of Slovenia, Miha Juhart, PhD, at the mourning session for Marko Ilešič, PhD, organised by the Faculty of Law of the University of Ljubljana and the Association of Law Societies of Slovenia at the Faculty of Law of the University of Ljubljana, on 28 June 2024. Marko Ilešič, PhD, was born in 1947, and was an outstanding lawyer, a Human with a capital “H”, a polyglot, and a sports enthusiast, particularly of football. He arguably left his greatest mark in his career as a judge of the Court of Justice of the European Union, where he served from 2004 until his untimely death. In the obituary, the author outlines some of the career achievements of the late Marko Ilešič, PhD, as well as his reputation among colleagues in law, sports, and beyond. As noted, Marko will be greatly missed by many.
Keywords: Ilešič, Marko; nekrologi; nogomet; pravniki; Sodišče Evropske unije; sodnik; šport; življenjepisi